2003
DOI: 10.1128/jvi.77.4.2436-2444.2003
|View full text |Cite
|
Sign up to set email alerts
|

Baculovirus Alkaline Nuclease Possesses a 5′→3′ Exonuclease Activity and Associates with the DNA-Binding Protein LEF-3

Abstract: Alkaline nuclease (AN) of the Autographa californica multiple-capsid nucleopolyhedrovirus (AcMNPV) (open reading frame 133) was expressed in recombinant baculovirus as a His 6 -tagged fusion and purified by sequential chromatography on Ni-NTA-agarose, DEAE-Toyopearl, and heparin-Sepharose. At all stages of purification, AcMNPV AN was found to copurify with a 44-kDa polypeptide which was identified as the baculovirus single-stranded DNA (ssDNA)-binding (SSB) protein, LEF-3. Sedimentation analysis in glycerol gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
61
0
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 38 publications
6
61
0
3
Order By: Relevance
“…Consistent with this model, ICP8 interacts with UL12 (53,55). Interestingly, Mikhailov et al have reported that the baculovirus alkaline nuclease associates with the DNA binding protein LEF-3, suggesting that baculovirus may also encode a two-subunit recombinase (30).…”
Section: Discussionsupporting
confidence: 54%
“…Consistent with this model, ICP8 interacts with UL12 (53,55). Interestingly, Mikhailov et al have reported that the baculovirus alkaline nuclease associates with the DNA binding protein LEF-3, suggesting that baculovirus may also encode a two-subunit recombinase (30).…”
Section: Discussionsupporting
confidence: 54%
“…Several of these auxiliary genes have homologues in MaviNPV, including ptp-1, ubiquitin, p10, superoxide dismutases (sod), v-cath, chitinase, ecdysteroid UDPglucosyltransferase (egt), actin rearrangement-inducing factor-1 (arif-1), alkaline exonuclease (alk-exo) and pk-1. The only auxiliary gene conserved among all baculoviruses is alk-exo, which interacts with lef-3, possesses both endoand exonuclease activities and can degrade both single-and double-stranded DNA in a 59-39 direction (Mikhailov et al, 2003). Two additional auxiliary genes with unknown function, viral fibroblast growth factor (vfgf) and ubiquitin, were also considered conserved among all lepidopteran baculoviruses (Herniou et al, 2003); surprisingly, no homologue of vfgf gene was found in MaviNPV.…”
Section: Sequence Analysis Of Mavinpv Genomementioning
confidence: 99%
“…LEF-3 also interacts with a viral alkaline nuclease (22), and it has been suggested that an alkaline nuclease-LEF-3 complex might be involved in repair and recombination of baculovirus genomes during replication. Because little is known about the mechanism of baculovirus replication, it will be of great interest to explore the functional role of other domains within LEF-3.…”
Section: Vol 79 2005mentioning
confidence: 99%